Development of Polymer Nanocomposites for Rapid Manufacturing Application - Wahab, M.S.; Dalgarno, K.W.; Cochrane, R.F. (International Journal of Integrated Engineering, 2009)
This paper presents initial development of polymer nanocomposites (PNC) material for rapid manufacturing (RM) application. PNC materials containing a polyamide (PA) and nano particles (5wt%) were produced by solution blending with the aim to improve the mechanical properties. Commercial polyamide 6 (PA6) was dissolved in formic acid (HCO2H) together with two different types of nano particle materials: yttrium stabilised zirconia (YSZ) and Hectorite clay (Benton 166) and spray-dried to create powder, creating powder with particle sizes in the range of 10-40 μm. The materials were processed on a CO2 selective laser sintering (SLS) experimental machine. Mechanical properties of the PNCs were evaluated and the results were compared with the unfilled base polymer. Good dispersion of additives was achieved by solution blending, however the PA6 was degraded during the material preparation and spray drying process which resulted in the formation of porous structure and low strength. However the addition of 5 (wt%) nano particles in the PA6 has shown to increase strength by an average of 50-60%. Further work on powder preparation is required in order to fully realise these performance benefits